Karapan Sapi Madura: An Analytical Study toward Potential Local Wisdom as Teaching Materials of Newtons’s Laws of Motion - Suliyanah, Suliyanah; Amiruddin, Mohd Zaidi Bin; Admoko, Setyo; Kholiq, Abdul; Zainuddin, Abu (Jurnal Pendidikan MIPA, 2023)
Developments in science and Indonesia continue to overgrow. One of them is proven by integrating knowledge through local wisdom in each of the studied knowledge. This study aims to explore and identify the potential of the local wisdom of Karapan Sapi Madura as teaching material on Newton's law material. This research uses qualitative descriptive type through Education analysis. Technique collection that data used is study literature, observation, and interviews. The results of this study present a linear study with knowledge of ethnoscience and ethnophysics on Karapan Sapi Madura. Besides that, study This study also found the potential for the local wisdom of the Madura Sapi Karapan to be used as teaching material on Newton's law material. In the future, local wisdom is expected of Karapan Sapi Madura that can be compiled in book form, e-books, or handouts that students and teachers can utilize to support learning physics by giving real examples and learning more meaning. In addition, it is also hoped that research related to wisdom locally is continuously developed and optimized for material learning, which is linear. Keywords: Indonesia local wisdom, physics learning, ethnophysics. DOI: http://dx.doi.org/10.23960/jpmipa/v24i2.pp406-418